The use of ICT to increase vaccination uptake: state of the evidence from experimental studies. (13th November 2019) - Odone, A; Balzarini, F; Frascella, B; Oradini Alacreu, A; Signorelli, C
Abstract: Background: Information and communication technology has a great potential to improve vaccine uptake by increasing the demand of vaccines and the supply of life-course immunization services. The EUVIS (EUrope Vaccines ICT Strategies) project aims at assessing the current use of ICT in European countries' immunization programs to inform the planning and implementation of ICT-based intervention models to increase vaccine uptake. Here we present the output of Part I of the EUVIS Project, the state of the evidence from experimental studies at the global and regional level. Methods: We conducted a systematic review following the PRISMA guidelines to analyze the available evidence from experimental studies on the impact of ICT-based interventions to improve: i) vaccine uptake (primary outcome), and other associated outcomes, including knowledge and attitudes towards immunization in infants, adolescents, adults, elder populations and at risk groups. Results: We included 68 RCTs. Informative websites significantly increased vaccination uptake among adolescents. Among young adults, none of the assessed interventions was successful in increasing vaccination uptake. The tools targeting parents that increased uptake were SMS, automated phone calls or messages, websites and online decision aid platforms. For pregnant women, combinations of more types of ICT were more effective in increasing uptake. In the adult population, both SMS and videos proved to be successful, while in elder populations and at-risk groups, the use of more traditional methods as short phone calls proved to be more efficient than ICTs. Conclusions: Technological innovations have made significant contributions to healthcare, but our results shows that the interventions must be tailored to target populations' specific characteristics and needs. These data are of crucial importance to identify which ICT-based interventions are more effective in each target group, to plan and implement immunization programs. Key messages: Information and Communication Technology-based interventions to increase vaccine uptake are more successful when planned tailoring target populations' specific characteristics and needs. ICT can significantly improve healthcare delivery but its role to increase vaccine uptake is controversial. Results from this systematic review are fundamental to plan tailored ICT-based interventions.